Pengaruh Pemahaman Panggilan Guru Kristen terhadap Pemberitaan Injil - Justin Niaga Siman Juntak (Sekolah Tinggi Teologi Torsina Surakarta, 2019)
Gospel preaching is a very important task, including Christian teachers who teach in schools. The entry of non-Christian teachers in YPK Pelita Pengharapan schools, moreover the subject of Islamic Education in two YPK Pelita Pengharapan Christian schools and being a teacher as a stepping stone to becoming civil servants indicates a weak preaching process in YPK Pelita Christian School Hope. The study was conducted to obtain empirical evidence about the influence of the understanding of Christian teacher's call to preaching the Gospel The Javanese Christian Church teachers in the Pelita Pengharapan Christian Education Foundation Research School were conducted in nine schools of the Pelita Pengharapan Christian Education Foundation spread in three sub-districts namely Patimuan, Sidareja, and Gandrungmangu. The data analysis method used is a simple regression analysis of 51 respondents. The results showed that the understanding of the Christian teacher's call had a positive and significant effect on the preaching of the Gospel of the Javanese Christian Church Teachers in the schools of the Pelita Pengharapan Christian Education Foundation, Cilacap Regency.AbstrakPemberitaan Injil merupakan tugas yang sangat penting, termasuk bagi para guru Agama Kristen yang mengajar di sekolah. Masuknya guru-guru non Kristen di sekolah-sekolah YPK Pelita Pengharapan, terlebih lagi mata pelajaran Pendidikan Agama Islam di dua sekolah Kristen YPK Pelita Pengharapan dan menjadi guru sebagai batu loncatan untuk menjadi Pegawai Negeri Sipil mengindikasikan proses pemberitaan Injil yang lemah di sekolah Kristen YPK Pelita Pengharapan. Penelitian dilakukan untuk memperoleh bukti empiris tentang pengaruh pemahaman tentang panggilan guru Kristen terhadap Pemberitaan Injil Guru-guru Gereja Kristen Jawa di sekolah-sekolah Yayasan Pendidikan Kristen Pelita Pengharapan Penelitian ini dilakukan di sembilan sekolah Yayasan Pendidikan Kristen Pelita Pengharapan yang tersebar di tiga kecamatan yaitu Patimuan, Sidareja dan Gandrungmangu. Metode analisis data yang digunakan adalah analisis regresi sederhana terhadap 51 responden. Hasil penelitian menunjukkan bahwa pemahaman panggilan guru Kristen berpengaruh positif dan signifikan terhadap pemberitaan Injil Guru-guru Gereja Kristen Jawa di sekolah-sekolah Yayasan Pendidikan Kristen Pelita Pengharapan Kabupaten Cilacap.